PERAN JENIS PEKERJAAN ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA KELAS V DI SDN 4 BANTRUNG - Dwi Wulandari; Wawan Shokib Rondli; Siti Masfuah (STKIP Subang, 2024)
This study examines the role of parental occupation in motivating fifth-grade students at SDN 4 Bantrung. Using a qualitative method, data were collected through in-depth interviews with students. Data analysis was conducted using the Miles and Huberman approach, which involves three main stages: data reduction, data presentation, and conclusion drawing.The results indicate that parental occupation significantly influences students' learning motivation. Students from less professional occupational backgrounds showed lower motivation compared to those from professional occupational backgrounds. The findings also highlight that family support, clear aspirations, rewards, and engaging activities play crucial roles in enhancing student motivation. Overall, active involvement and strong support from the family, as well as the relevance of learning activities, significantly impact students' motivation to study diligently.